Konversi Agama di Kalangan Milenial (Fenomena Hijrah: Felix Siauw) - Mutia Ainun Nabila; Riski Mayang Sari; Khoiriyah Ulfa (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This paper raises a story which is the experience of a person's conversion from the religion he adhered to since childhood which has been passed down from generation to generation and appears with a new religion, namely Felix Siauw. Felix Siauw is a convert who is now an ustadz who is active in preaching. Felix Siauw's journey of hijrah as a form of religious conversion went through quite a long stage. He was in a phase of anxiety about the presence of God, then went through a phase of God's presence in his life, which ultimately led him to the stage of religious conversion until he joined a religious organization. In the process of his migration he was influenced by various factors which ultimately made him carry out a total religious conversion, including the factors of conflict, emotions, adolescence, and will. This paper aims to describe the phenomenon of Felix Siauw's migration in terms of religious conversion, both traditional and contemporary conversions. In this study, the authors used the literature study method both from book sources, journals, news, and videos that were relevant to the research object. Keyword: Migration, Religious Conversion, Felix Siauw